2022
DOI: 10.3390/foods11162499
|View full text |Cite
|
Sign up to set email alerts
|

Si-Wu Water Extracts Protect against Colonic Mucus Barrier Damage by Regulating Muc2 Mucin Expression in Mice Fed a High-Fat Diet

Abstract: A high-fat diet (HFD) could cause gut barrier damage. The herbs in si-wu (SW) include dang gui (Angelica sinensis (Oliv.) Diels), shu di huang (the processed root of Rehmannia glutinosa Libosch.), chuan xiong (rhizome of Ligusticum chuanxiong Hort.), and bai shao (the root of Paeonia lactiflora f. pilosella (Nakai) Kitag.). Si-wu water extracts (SWE) have been used to treat blood deficiency. Components of one herb from SW have been reported to have anti-inflammatory and anti-obesity activities. However, there … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Colon innervating TRPA1 and TRPV1 +ve peptidergic sensory neurons regulate intestinal pain during inflammatory conditions like IBD , and are crucial for colonic mucosal health. ,, Our group’s previous research demonstrated the functional role of TRPA1 and TRPV1 channels in the regulation of intestinal mucus homeostasis. ,, CPZ administration inhibits TRPA1- and TRPV1-mediated nociceptive response and has been proposed as a possible candidate for therapeutics for IBD . However, it also reduces gastrointestinal mucus production and alters gut barrier integrity, which contrasts to its protective effects. , HFD feeding has detrimental effects on glucose homeostasis, mucus content in the colon, and gut barrier integrity. ,, Hence, considering the clinical scenario, we studied how HFD consumption affects the colonic mucosal health of mucosal compromised patients (CPZ administered). Furthermore, the efficacy of prebiotics in these conditions was tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colon innervating TRPA1 and TRPV1 +ve peptidergic sensory neurons regulate intestinal pain during inflammatory conditions like IBD , and are crucial for colonic mucosal health. ,, Our group’s previous research demonstrated the functional role of TRPA1 and TRPV1 channels in the regulation of intestinal mucus homeostasis. ,, CPZ administration inhibits TRPA1- and TRPV1-mediated nociceptive response and has been proposed as a possible candidate for therapeutics for IBD . However, it also reduces gastrointestinal mucus production and alters gut barrier integrity, which contrasts to its protective effects. , HFD feeding has detrimental effects on glucose homeostasis, mucus content in the colon, and gut barrier integrity. ,, Hence, considering the clinical scenario, we studied how HFD consumption affects the colonic mucosal health of mucosal compromised patients (CPZ administered). Furthermore, the efficacy of prebiotics in these conditions was tested.…”
Section: Discussionmentioning
confidence: 99%
“…18,21 HFD feeding has detrimental effects on glucose homeostasis, mucus content in the colon, and gut barrier integrity. 7,23,24 Hence, considering the clinical scenario, we studied how HFD consumption affects the colonic mucosal health of mucosal compromised patients (CPZ administered). Furthermore, the efficacy of prebiotics in these conditions was tested.…”
Section: Discussionmentioning
confidence: 99%
“…(8) TNF‐α can induce MUC1 gene transcription by activating the MEK1/2/ERK1/Sp1 pathway 52,53 . (9) TNF‐α can induce MUC2 gene transcription by activating the PKC/TK pathway 40,41 …”
Section: Characteristics Of Mucin Hypersecretion In Different Endotyp...mentioning
confidence: 99%
“…proposed the following mechanism by which TNF‐α might induce MUC5AC gene expression: TNF‐α activates mitogen, mitogen‐ and stress‐activated protein kinase 1(MSK1), cAMP response element‐binding protein, and cAMP response element through ERK1/2 and p38MAP kinases, thereby causing a signaling cascade and inducing Muc5ac gene expression 39 . In human lung mucoepidermoid cancer cell lines, TNF‐α mediates MUC‐2 gene expression via the protein kinase C and tyrosine kinase signal transduction pathways in a concentration‐dependent manner 40,41 . However, with the increase in goblet cells, mucus gels are formed in the inflammatory region, and make it difficult for TNF‐α to bind with its receptors.…”
Section: Characteristics Of Mucin Hypersecretion In Different Endotyp...mentioning
confidence: 99%
See 1 more Smart Citation